ANALISIS PENGARUH LEVERAGE DAN LIKUIDITAS TERHADAP PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY PADA PERUSAHAAN MANUFAKTUR SUB-SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2016 - 2018 - Jojor Togi Marito Simamora; Rina Dameria N Rina Dameria N (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2020)
Liquidity and Leverage Influencers on Corporate Social Responsibility aims to examine the effect of whether Liquidity and Leverage affect corporate responsibility in the mining sub-sector manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the period of 2016 – 2018. The method used in this study is the multiple regression method to determine the effect of the variables related in the study. The results of the study revealed a simultaneous F test that was calculated value F = 15,112. a value of 15,112> 3.47 thus Ho is rejected and H3 is accepted, meaning that there is an effect between Liquidity (X1) and leverage (X2) simultaneously on the Corporate Social Responsibility of companies listed on the Indonesia Stock Exchange in 2016-2018 (Y).